A noção de representação na Crítica da Razão Pura - Cunha, Peterson Kenji da (Universidade Federal de São Carlos, 2021)
The term representation is present throughout the Critique of Pure Reason, a clear indication of its importance for Kant´s critical investigation. However, despite the assumed importance, at each moment, the use of this term does not seem to indicate or mean the same thing. For this reason, the concept of representation can be considered not only complex, but also diffuse; moreover, this difficulty increases considerably since the notion of representation is, according to Kant, conceptually indefinable. On the one hand, in Jäsche's Logic, Kant maintains that the notion of representation is always presupposed in the the structure of knowledge. On the other hand, both in the Inaugural Dissertation and in the Critique of Pure Reason, there is no attempt to explain this concept satisfactorily, which justifies an extensive investigation of the concept of representation in the first Critique. Our aim is to carry out an analysis of the problem of representation in Kant's theoretical philosophy. It is important to determine how the concept of representation, which cannot be defined, appears in some moments of the Inaugural Dissertation and the Critique of Pure Reason. The last and crucial allows to shed light on how the representation can refer to the consciousness, understood as a the highest principle of all knowledge.
The notion of representation in the Critique of Pure Reason
Keywords: Kant; Crítica da razão pura; representação; Dissertação de 70; Consciência; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA